2014
DOI: 10.1111/jomf.12098
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Incarceration and the Housing Security of Urban Mothers

Abstract: High rates of imprisonment among American fathers have motivated an ongoing examination of incarceration’s role in family life. A growing literature suggests that incarceration creates material and socioemotional challenges not only for prisoners and former prisoners but also for their families and communities. The authors examined the relationship between fathers’ incarceration and one such challenge: the housing insecurity of the mothers of their children. Using data from the Fragile Families and Child Wellb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 73 publications
(78 reference statements)
2
71
1
Order By: Relevance
“…First, these dimensions of children's lives are linked to each other. Changes in family structure affect residential mobility: children whose parents separate or divorce are highly likely to experience residential moves (Astone & McLanahan, 1994;South, Crowder & Trent, 1998), as are children whose parents become unemployed or change jobs (Clark & Davies Withers, 1999) or become incarcerated (Geller & Franklin, 2014). Second, overlapping mechanisms underlie the impact of each dimension on child wellbeing.…”
Section: Childhood Residential Mobility In Contextmentioning
confidence: 99%
“…First, these dimensions of children's lives are linked to each other. Changes in family structure affect residential mobility: children whose parents separate or divorce are highly likely to experience residential moves (Astone & McLanahan, 1994;South, Crowder & Trent, 1998), as are children whose parents become unemployed or change jobs (Clark & Davies Withers, 1999) or become incarcerated (Geller & Franklin, 2014). Second, overlapping mechanisms underlie the impact of each dimension on child wellbeing.…”
Section: Childhood Residential Mobility In Contextmentioning
confidence: 99%
“…A binary dependent variable defines housing instability for families who experienced one of the following living conditions in the past 12 months: (1) missed rent or mortgage payment, (2) moved-in with others (double-up), (3) moved more than once, (4) evicted, or (5) were homeless or stayed at a shelter/abandoned building/automobile (Curtis et al 2014;Fertig and Reingold 2008;Geller and Franklin 2014). Moving-in with others, also known as doubling-up, can also serve as a safety net (Pilkauskas et al 2014).…”
Section: Datamentioning
confidence: 99%
“…In an empirical analysis, O'Flaherty (2009) found evidence that income shocks were a principal source of housing insecurity. Curtis et al (2013) found that shocks in the form of the birth of a child with a severe health problem increased the risks of homelessness, while Geller and Franklin (2014) found that a partner's incarceration contributed to homelessness.…”
Section: Previous Studiesmentioning
confidence: 99%
“…O'Flaherty (2004;2010) has theorised that homelessness is often unpredictable and largely the result of negative, bad-luck shocks hitting people who were otherwise vulnerable. Research has found supporting evidence regarding shocks from income losses (O'Flaherty, 2009), a partner's incarceration (Geller & Franklin, 2014), and the birth of children with severe health problems (Curtis et al, 2013). Physical violence, which occurs infrequently and unpredictably for the vast majority of people, has properties of a shock.…”
mentioning
confidence: 99%